Sequência didática para o ensino de eletromagnetismo usando aplicativo para smartphone - Santos, Antonio Ricardo Queiroz dos (2018)
Throughout the High School is presented to the student all branches of Classical Physics. This process is full of mishaps, frustrations and rejection. From there, in an attempt to minimize rejection to physics, we develop an educational sequence and, investigate his efficiency in the teaching of the electromagnetism with the help of a virtual environment, mediated by the teacher. For that a cellphone applications program was chosen, more precisely Physics in the School, because of being treated as a resource easy to get to, which does not need a laboratory environment. Being his possible application in any environment, since almost the totality of the current pupils have of smartphones compatible with the applications program. The research was based on the authors' work like VYGOTSKY, VERGNAUD and AUSUBEL, and showed quite satisfactory results regarding the learning of the cited content. Since we have obtained, among other positive factors, a greater interest of the students to participate in the process of teaching and learning. There with, we realized not only that learning was more significant, but also, we can detect the main deficiencies to acquire a concrete and lasting knowledge and correct them.